Reconsidering the origins of the Southern African regionalism thirty years later: towards a constructivist approach to the origins of SADC - José Abel Moma (Janus.net, 2012)
The creation of SADCC has generated a debate over the real origins of the southern African model of regionalism. This paper develops the idea that the origins of SADC are both internal and external. Thus, southern African regionalism is understood as a constructivist articulation of internal and external inputs, which determined the creation of SADCC and its transformation into SADC.